PENGUATAN KREATIVITAS DAN KEMANDIRIAN PESERTA DIDIK MELALUI PENDIDIKAN ENTREPRENEURSHIP - Nisrina Qurrotul Ain; Nadzifah A’isyah Fauzi; Rahma Nafalina Azzahra; Neza Dwi Nasyfa; Ferida Rahmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the role of entrepreneurship education in strengthening students’ creativity and independence in educational settings. The problem addressed in this study is the relatively low level of creativity and independence among students, reflected in their dependence on teachers, lack of confidence in expressing ideas, and limited problem-solving abilities. This research employs a qualitative approach using a literature review method. Data were collected from secondary sources, including scientific journals, books, and relevant academic articles, and analyzed through content analysis to identify major concepts, compare expert perspectives, and synthesize findings systematically. The results indicate that entrepreneurship education plays a significant role in enhancing students’ creativity and independence through project-based learning, experiential activities, and entrepreneurship-oriented programs such as the Projek Penguatan Profil Pelajar Pancasila (P5). These approaches encourage students to think creatively, solve problems independently, build self-confidence, and develop responsibility. However, the implementation of entrepreneurship education still faces several challenges, including limited facilities, insufficient teacher readiness, students’ varying levels of understanding, and time constraints. Therefore, improving practical, innovative, and sustainable entrepreneurship education is essential to maximize its effectiveness in fostering adaptive, creative, and independent learners.